Предмет: Математика,
автор: bagdanmatvienkoBM
Решите пожалуйста уравнения:
1) (х+4,5)(6х-1)-(3х+1,6)(2х-1)=-3,8х
2) (3,5-х)(7х+2)+(3,5х-1)(7+2х)=-450
Ответы
Автор ответа:
3
Ответ:
Пошаговое объяснение:
1) (х+4,5)(6х-1)-(3х+1,6)(2х-1)=-3,8х
6х²-х+27х-4.5-6х²+3х-3.2х+1.6=-3.8х
-х+27х+3х-3.2х+3.8х=-1.6+4.5
29.6х=2.9
х=2.9:29.6
х=29\296
2) (3,5-х)(7х+2)+(3,5х-1)(7+2х)=-450
24.5х+7-7х²-2х+24.5х+7х²-7-2х=-450
24.5х-2х+24.5х-2х=-450
45х=-450
х=-450:45
х=-10
bagdanmatvienkoBM:
Thank you bro
Похожие вопросы
Предмет: Биология,
автор: Chucha331
Предмет: Математика,
автор: gorbarbaryan
Предмет: Литература,
автор: toxamedni2208gmailc
Предмет: История,
автор: ClubNezer